Optimalisasi Teknologi Dan Kesehatan Untuk Mewujudkan Masyarakat Sejahtera Di Desa Gatak - Al-Falaq, Muhammad Akbar; Salsabila, Najwa; Agnazahra, Batrisya Aida; Fauziah, Shafira Nathania; Anggraini, Silva; Rizqi, Alya Husnia; Cahyani, Anisa; Fitri, Louh Dinda Rizki; Syafiq, Farhan; Hirzi, Akaiella Daffa; Setyawan, Haris (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
he community service program titled “Sehati (Sehat Tanpa PTM Periksa Kesehatan Lagi)” was implemented in response to the high prevalence of Non-Communicable Diseases (NCDs) in Gatak Village, Ngawen District. The program aimed to raise awareness and enhance public understanding of the importance of a healthy lifestyle and early detection of NCDs such as hypertension, diabetes, uric acid, and high cholesterol. The methods employed included health education, physical activity through regular aerobic exercises, free health screenings, and blood donation events. Activities were carried out in a participatory and interactive manner, involving local residents at every stage, from outreach to mentoring. The results demonstrated a significant improvement in knowledge, attitudes, and health-related behaviors among the community. Around 50 individuals regularly participated in weekly exercise sessions, and the health screenings showed improvements in key indicators for many participants. The blood donation event, conducted in collaboration with the Indonesian Red Cross (PMI), successfully collected 80 bags of blood and raised awareness about the social and health benefits of blood donation. Comprehensive evaluation revealed that this educational approach combined with direct intervention was effective in promoting healthy behavior changes and presented opportunities for sustainable local health policy development. The success of this program highlights the effectiveness of integrating education, screening, and community empowerment as a strategy to reduce NCD rates in rural areas.